2018
DOI: 10.1093/ajcn/nqy007
|View full text |Cite
|
Sign up to set email alerts
|

Changes in susceptibility to life-threatening infections after treatment for complicated severe malnutrition in Kenya

Abstract: BackgroundGoals of treating childhood severe acute malnutrition (SAM), in addition to anthropometric recovery and preventing short-term mortality, include reducing the risks of subsequent serious infections. How quickly and how much the risk of serious illness changes during rehabilitation are unknown but could inform improving the design and scope of interventions.ObjectiveThe aim of this study was to investigate changes in the risk of life-threatening events (LTEs) in relation to anthropometric recovery from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 33 publications
1
17
1
Order By: Relevance
“…Children with cSAM were actively linked to therapeutic and supplementary feeding programmes upon hospital discharge. Missing follow‐up visits and needing to be traced by a fieldworker making a home visit was associated with readmission (with any condition, not just complicated SAM) and death, as previously published (Berkley et al, ; Ngari et al, a).…”
Section: Methodssupporting
confidence: 69%
See 3 more Smart Citations
“…Children with cSAM were actively linked to therapeutic and supplementary feeding programmes upon hospital discharge. Missing follow‐up visits and needing to be traced by a fieldworker making a home visit was associated with readmission (with any condition, not just complicated SAM) and death, as previously published (Berkley et al, ; Ngari et al, a).…”
Section: Methodssupporting
confidence: 69%
“…The goal of SAM treatment also includes the reduction of susceptibility to life‐threatening infections, restoration of a healthy body composition, and improvement in neurocognitive status (Ngari et al, a). However, children with SAM remain at risk of developing severe illness and/or infections after treatment of clinical complications and discharged from hospital (Berkley et al, ; Chisti et al, ; Kerac et al, ; Ngari et al, a). A study by Kerac et al () that followed 1,024 children 1 year post‐discharge reported 5% hospital readmissions but 42% deaths, whereas Khanum et al () reported 1.2% emergency hospital readmissions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, when all anthropometric measures (eg, height, weight, BMI, MUAC) in a given population of undernourished children are represented by z-scores, the extent to which each measure deviates from the mean will differ depending on the presence of other confounders such as wasting, stunting, dehydration, and edema. [28][29][30][31] In our cohort, for example, MUACz was 0.4 SD lower than the mean, whereas BMIz or WLz were only 0.1 SD below the mean despite the fact that weight and height, independently, were 0.5 and 0.8 SD below the mean, respectively. Consequently, it is unclear whether the same z-score thresholds should be applied across parameters to classify malnutrition.…”
Section: Discussionmentioning
confidence: 99%